Analisis Energi Aktual Purata per Minggu yang Dihasilkan Solar Panel 20 WP di Kota Bekasi - Afiff, Jamal M; Alamhudi, Gusti Firdaus (MESIN, 2019)
Solar panel is gaining popularity as one of the source of alternative energy especially in tropical country. Solar panel users need to know how much energy is produced and what components it takes before starting to make a solar panel system. A comparison between ideal energy and actual energy will help to evaluate the performance of solar panel to show how much energy it will produce under a real condition. In this research, a 20 WP solar panel was used and the data collection was performed from 9 May 2018–9 July 2018 in Bekasi City. Collected data are voltage and current produced by the solar panel every ten minutes for ten hours continuous measurements. The solar panel performance was analysed by comparing maximum power, average power, and energy production per week. From the data measurements and analysis, it is found that the total energy produced is 3797 Wh, the average energy produced in one day is 61.24 Wh, and the average peak hour is 11.20 a.m.